Perancangan Arsitektur RESTful pada Integrasi Data Refrensi Buku di Perpustakaan Daerah dan Perpustakaan Universitas (Studi Kasus: Kota Salatiga) - Erwien Christianto; Joko Santosa (Institut Agama Islam Negeri Salatiga, 2018)
The library in this modern era in the advancement of information technology needsto be developed towards data integeration. Network communication between librariescan be a means of good learning, effective and efficient. The problem often encounteredin collaborating on the business process for integeration of library data is the differenceof application to the user of each part. Technology that can integrate data eventhough different applications / platforms on end users with web service technology.With the web service for RESTFul method can bridge the integration of data exchangefor book refrence in library so that can be know where and where book have referencesto references book or document needed. Restful technology is created with java classand database as prototype and simulation. Clear and viable business processes can beintegrated into an integrated information system.